The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10549-006-9328-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of interleukin-6 (IL-6) in breast cancer (review)

Abstract: Cytokines are factors that are known to have both tumor-promoting and inhibitory effects on breast cancer growth depending presumably on their relative concentrations and the presence of other modulating factors. Different cytokines play an important role in controlling the immune system. Interleukin-6 (IL-6) is a pleiotropic cytokine with obviously tumor-promoting and tumor-inhibitory effects. Here, we review the role of IL-6 in in vitro experiments of breast tumor cells, in breast tumor tissues (BTs) and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
284
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(311 citation statements)
references
References 43 publications
10
284
1
7
Order By: Relevance
“…Smoking is associated with increased serum levels of the cytokine IL-6 and C-reactive protein (CRP) [13]. Several small case-control studies have suggested serum IL-6 is increased in women with breast cancer [14]. Recently, Il'yasova et al [15] reported increased serum CRP was associated with incident breast cancer in a cohort of post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is associated with increased serum levels of the cytokine IL-6 and C-reactive protein (CRP) [13]. Several small case-control studies have suggested serum IL-6 is increased in women with breast cancer [14]. Recently, Il'yasova et al [15] reported increased serum CRP was associated with incident breast cancer in a cohort of post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…13 There are consistent data showing increased levels of IL-6 in breast cancer patients when compared with healthy controls and increased levels of IL-6 have also been correlated with clinical tumor stage, lymph node infiltration and recurrent disease. 46 IL-6 levels have also been associated with poor prognosis for time-to-progression and death in advanced stage patients. 47 In summary, we report for the first time that ablation of MCP-1 expression through genetic deletion delays mammary tumorigenesis and downregulates localized inflammation in the C3(1)/SV40Tag model of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the disease usually takes aggressive course where the IL-6 level is found to be elevated thereby indicating possibility of it being used as prognostic marker [9]. It is accepted that IL-6 promotes tumoral growth by upregulating antiapoptotic and angiogenic proteins in tumor cells [4][5][6]. Levels of IL-6 are reported to be considerably high in cancer patients compared to healthy control subjects [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…According to a comprehensive review on the role of Il-6 in carcinogenesis, by Knüpfer and Preiss [6], serum IL-6 emerged as a negative prognosticator in breast cancer patients. Our data from Indian subset of patients also supports the same by virtue of increasing Il-6 titers with advanced stage, adipose tissue invasion, mitotic index and axillary lymph node involvement in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation